2016
DOI: 10.1590/s1517-707620160004.0091
|View full text |Cite
|
Sign up to set email alerts
|

Carbon steel corrosion induced by sulphate-reducing bacteria in artificial seawater: electrochemical and morphological characterizations

Abstract: In this work, the corrosion behavior of carbon steel AISI 1020 was evaluated in artificial seawater in the presence of mixed sulfate-reducing bacteria (SRB) culture isolated from the rust of a pipeline. The corrosion evaluation was performed by electrochemical techniques (open circuit potential (E ocp ), polarization curves and electrochemical impedance spectroscopy (EIS)), while the formation of a biofilm and corrosion products were observed by scanning electron microscopy (SEM) and X-ray energy dispersive sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…MIC materialises after the production of a biofilm on the surface of the steel 11,12) . In the course of SRB's metabolic activity, reduction of sulfate ions occurs into three forms of sulfide ions, namely H2S (soluble), HSand S [2][3][4][5][6][7][8][9][10][11][12][13]14) . The company of carbon dioxide (CO2), hydrogen sulphide (H2S), seawater and other particles initiate critical corrosion-related problems in oil and gas pipelines.…”
Section: Introductionmentioning
confidence: 99%
“…MIC materialises after the production of a biofilm on the surface of the steel 11,12) . In the course of SRB's metabolic activity, reduction of sulfate ions occurs into three forms of sulfide ions, namely H2S (soluble), HSand S [2][3][4][5][6][7][8][9][10][11][12][13]14) . The company of carbon dioxide (CO2), hydrogen sulphide (H2S), seawater and other particles initiate critical corrosion-related problems in oil and gas pipelines.…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between the metal surface and the biofilm may then alter the kinetics of anodic/cathodic reactions occurring during electrochemical processes. Biofilm formation may enhance metal deterioration [34] by affecting the physico-chemical properties of the metal surface or by altering the properties of the passivation layer [11]. On the other hand, biofilms can also have a passivation effect, protecting the metal surface against corrosion [35].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, several studies have reported MIC on stainless steel, carbon steel and P235GH steel materials under repository relevant conditions [4,[34][35][36][37]. A recent study on MIC of carbon steel exposed to anaerobic soil using conventional electrochemical techniques demonstrated localised corrosion on the steel surface accompanied by breakdown of the biogenic ferrous sulphide (FeS) film [38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation